2017
DOI: 10.21111/dnj.v1i1.1020
|View full text |Cite
|
Sign up to set email alerts
|

Faktor – Faktor Yang Mempengaruhi Kebiasaan Memeriksa Label Halal Kemasan Pangan Pada Santriwati

Abstract: Choosing halal food and beverages is the duty of every ABSTRAK Memilih makanan dan minuman yang halal adalah kewajiban dari setiap muslim. Hal ini diaplikasikan dalam kehidupan sehari-hari, salah satunya adalah dengan memperhatikan kehalalan apa yang akan dikonsumsi dengan memeriksa informasi kehalalan produk pada label kemasan. Metode penelitian yang digunakan adalah metode survey dengan pendekatan potong lintang (Crossectional). Penelitian dilakukan di Pondok Modern

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…The effectiveness of label utilization as a source of product information and quality depends on consumer awareness and understanding of the information (Damayanti & Rimbawan, 2016). Research conducted by Fathimah (2017) showed a significant relationship between knowledge and the habit of checking packaging labels in grade VI Santriawati. The research results by Melinda and Farida (2021) also show a relationship between knowledge and the behavior of reading information on packaging.…”
Section: Conceptual Frameworkmentioning
confidence: 97%
See 1 more Smart Citation
“…The effectiveness of label utilization as a source of product information and quality depends on consumer awareness and understanding of the information (Damayanti & Rimbawan, 2016). Research conducted by Fathimah (2017) showed a significant relationship between knowledge and the habit of checking packaging labels in grade VI Santriawati. The research results by Melinda and Farida (2021) also show a relationship between knowledge and the behavior of reading information on packaging.…”
Section: Conceptual Frameworkmentioning
confidence: 97%
“…However, there was a tendency toward higher reading behavior in rural areas than in urban areas. Consuming food in Islam is not just to eliminate hunger or physical needs but also to consider whether it contains halal or haram things (Fathimah, 2017). Of course, the halal label is very important to pay attention to because it is related to the guarantee for Muslims that certain products are suitable for consumption.…”
Section: The Effect Of Knowledge On Food Label Reading Behavior Adole...mentioning
confidence: 99%
“…Berdasarkan hasil penelitian ditemukan bahwa prevalensi santriwati memeriksa label halal sebesar 67%. Faktor yang memiliki hubungan yang bermakna (p < 0.05) dengan kebiasaan memeriksa label halal produk yaitu: sikap, pengetahuan label halal, membaca nama produk, membaca komposisi produk, membaca berat bersih, membaca harga, membaca nilai gizi dan kadaluarsa produk (Fathimah Fathimah, 2017).…”
Section: Tabel 4 3 Koefesien Korelasi Dan Determinasiunclassified